Preparation of quaternized chitosan/Ag composite nanogels in inverse miniemulsions for durable and antimicrobial cotton fabrics. (15th February 2022) - Gao, Feng; Mi, Yifang; Wu, Xinlei; Yao, Jun; Qi, Qi; Chen, Wei; Cao, Zhihai
Abstract: It is an urgent task to exploit effective antimicrobial agents due to the rise of drug-resistant pathogens. Herein, antimicrobial quaternized chitosan/Ag composite nanogels (QCS/Ag CNGs) with tunable properties were fabricated through inverse miniemulsion technique with a high encapsulation efficiency of NH2 -Ag nanoparticles (NPs). The QCS/Ag CNGs possess superior broad-spectrum antimicrobial activity and low biotoxicity, via synergistic sterilization of Ag NPs and QCS. Furthermore, the NH2 -Ag NPs were chemically linked to the QCS matrix through Schiff base reactions, and the QCS/Ag CNGs have reactive groups, making it possible to obtain durable antibacterial cotton fabrics. Thus, QCS/Ag CNGs modified cotton fabrics exhibited laundering durability of antimicrobial effect after 100 washing cycles without sacrificing other inherent properties of cotton fabrics. Our study provides a facile and controllable method to construct polymer/inorganic CNGs to address the urgent need for antibacterial agents/fabrics. Graphical abstract: Unlabelled Image Highlights: QCS and Ag NPs were composited efficiently via inverse miniemulsion. QCS/Ag composite nanogels (QCS/Ag CNGs) exhibited tuned properties. Effective antimicrobial and excellent biocompatibility realized through synergic mechanism. QCS/Ag CNGs endowed durable antimicrobial activity to the modified cotton fabric. The modified cotton fabrics maintained other inherent properties.